Situational analysis to inform resource sharing agreement in Karamoja Cluster - Kenduiywo, Benson; Chepngetich, Brenda; Korir, Victor; Ogero, Derrick; Denje, Telvin; Juma, Quinto (2024)
This report provides critical scientific evidence to inform the Kenya-Uganda Resource sharing agreement deemed relevant following allegations by the Ugandan government against Turkana pastoralists. These claims led to the arrest and ban of Turkana herders from Uganda. This report presents a situational analysis of the Karamoja Cluster focusing on natural resources such as water and pasture, impacts of climate change and threats posed by climatic hazards, locust and invasive species. Findings highlight that Karamoja faces significant risks from droughts, floods and heat stress with future projections indicating an increase in hazards. Furthermore, invasive species and locust infestation are a prevalent concern threatening pasture availability. To address these challenges, the report emphasizes the need for targeted interventions to curb the spread of invasive species, mitigate climate hazards and promote resilience. Lastly, communities need to explore alternative livelihoods to reduce vulnerabilities. This evidence-based analysis is a step towards fostering peace and promoting sustainable resource management and strengthening cross-border collaboration between Kenya and Uganda.